BENTUK PENYAJIAN TARI GALOMBANG PRODUKSI SANGGAR RAJO BATUAHDALAM PESTA PERKAWINAN DI KOTA PAYAKUMBUH - Eliska, Putri; Mansyur, Herlinda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to describe and reveal the presentation form of the Galombang Dance produced by the Rajo Batuah Studio at wedding celebrations in Payakumbuh City. This type of research is qualitative with an analytical descriptive method. The research instruments are the researcher themselves, assisted by writing tools and a camera. Data was collected through literature studies, observations, interviews, and documentation. The steps for data analysis include data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that the form of presentation of the Galombang Dance produced by the Rajo Batuah Studio at wedding celebrations in Payakumbuh City consists of movement, dancers, floor patterns, makeup and costumes, properties, music, and performance locations. The Wave Dance Movements in silat consist of 10 types of movements: the sambah pambukak movement, the mambukak langkah movement, the tusuak sampiang movement, the malangkah ka balakang movement, the gajah maram movement, the ayun sampiang movement, the sauak movement, the langkah kiri kanan movement, the tusuak puta movement, and the tusuak layang movement. Furthermore, there are 15 types of movements for female dancers: the maayun ateh bawah movement, the lapiak jarami movement, the dorong sampiang puta movement, the mayilamg ateh movement, the tusuak ateh movement, the ambiak silang movement, the mambukak langkah movement, the ayun puta movement, the transisi movement, the manyonsong movement, the manyonsong puta movement, the ambiak puta movement, the manyonsong movement, the manyonsong puta movement, and the ambiak puta movement. The Galombang Dance is performed by 2 martial artists, 5 dancers and 1 person carrying the carano. The floor pattern in this dance forms a horizontal line, with the carano positioned in the middle at the back row. The dancers wear costumes and makeup that vary according to the needs of the performance. For the female dancers, the costumes and makeup are adapted to the Minangkabau traditional attire, namely the baju kurung paired with the kodek or songket cloth, and complemented with accessories. The costume designer for the male musicians in Sanggar Rajo Batuah also aligns their outfits with those of the dancers and martial artists in the Galombang Dance. The accompanying music used in this performance includes talempong, tasa, floor, bansi, hit – hat, and bass. Each musical instrument is played by one musician. The Galombang Dance is performed outside the wedding venue of the newlyweds.